Advances in Forming, Machining and Automation Proceedings of AIMTDR 2018 - Shunmugam, M. S.; Kanthababu, M.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume comprises select proceedings of the 7th International and 28th All India Manufacturing Technology, Design and Research conference 2018 (AIMTDR 2018). The papers in this volume focus on forming and machining, and discuss both conventional technologies and the latest developments and innovations, including both experimental studies and simulations; while those on automation present the latest research on hardware as well as software aspects. This volume will be of interest to researchers, and practicing engineers alike.
Effect of Heat Treatment on Formability of AA6082 by Single Point Incremental Forming -- Forming Behavior of AA5052-H32 & AA6061-T6 During Single Point Incremental Forming -- Pull out Forming: Experiments and Process Simulation -- Failure Prediction and Forming Behavior of AA5754 Sheets at Warm Temperature -- Magnetic Pulse Forming and Punching of Al Tubes - A Novel Technique for Forming and Perforation of Tubes -- Experimental Investigation on the Forming of AA 5052-H32 Sheet Using a Rigid Body Based Impact in a Shock Tube.
Keywords: Coatings; Tribology; Corrosion and anti-corrosives.; Manufactures; Machinery; Surfaces (Technology).; Thin films; Coatings; Tribology; Corrosion; Machines, Tools, Processes; Machinery and Machine Elements; Surfaces, Interfaces and Thin Film